Implicit and Explicit Processes in Risk Perception: Neural Antecedents of Perceived HIV Risk - Schmälzle, Ralf; Schupp, Harald T.; Barth, Alexander; Renner, Britta (Frontiers in Human Neuroscience, 2011)
Field studies on HIV risk suggest that people may rely on impressions they have about the safety of their partner at the dispense of more objective risk protection strategies. In this study, ERP recordings were used to investigate the brain mechanisms that give rise to such impressions. First, in an implicit condition, participants viewed a series of photographs of unacquainted persons while performing a task that did not mention HIV risk. Second, in an explicit condition, participants estimated the HIV risk for each presented person. Dense sensor EEG was recorded during the implicit and explicit conditions. In the analysis, explicit risk ratings were used to categorize ERP data from the implicit and explicit conditions into low and high HIV risk categories. The results reveal implicit ERP differences on the basis of subsequent ratings of HIV risk. Specifically, the processing of risky individuals was associated with an early occipital negativity (240 - 300 ms) and a subsequent central positivity between 430 and 530 ms compared to safe. A similar ERP modulation emerged in the explicit condition for the central positivity component between 430 and 530 ms. A subsequent late positive potential component between 550 and 800 ms was specifically enhanced for risky persons in the explicit rating condition while not modulated in the implicit condition. Furthermore, ratings of HIV risk correlated substantially with ratings of trustworthiness and responsibility. Taken together, these observations provide evidence for theories of intuitive risk perception, which, in the case of HIV risk, seem to operate via appearance-based stereotypic inferences.